16th UC Berkeley Heavy Held at Red Lion Inn-Sacramento - Watkins, Howard::::::::: (1984)
Denise Morse, Bonnie Neary, and Cathy Barkett having dessert; Frank Gumpert and Jerry Neary behind ? In green shirt